Action distance as a predictor of winning and losing matches at FIVB Volleyball Men's World Championship - Dariusz Mroczek; Damian Pawlik (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: Technology determines the emergence of functional tools to monitor and control motor activity during the game. One of the solutions for monitoring the player in indoor sports are computer video analyses, which determine basic kinematic parameters. The study aims to compare team and player activity with the outcome of a given set and the effect of the game status on player activity during a championship-level match. Materials and Methods: The study analysed 140 volleyball players aged 19 to 40 years (27.05 ± 4.33 years, height: 197.15 ± 9.63 cm, body mass: 88.51 ± 9.23 kg) participating in the FIVB Volleyball Men's World Championship. The observed matches were categorised by score (3:0, 3:1, 3:2 and 0:3, 1:3 and 2:3). Depending on winning or losing, each set was described as W - a winning set, P - a losing set and O - as the first set. Results: The average distance covered in all observed matches was 10.7 ± 0.09 m, while for matches completed in 3 sets, it was 10.48 ± 0.13 m. Attackers covered the longest distance in action (11.43 ± 1.68 m), while the libero covered the shortest distance from among all observed players (8.79 ± 1.91 m). The losing teams covered a significantly greater distance in action (10.87 ± 2.24 m) in action than the winning teams (10.54 ± 1.91 m). Conclusion: The results of this study allow the conclusion that teams winning sets cover a smaller average distance in action than their opponents. The highest covered distance was observed in the first set and in sets 4 and 5 when teams were losing a set after losing the previous one. The smallest distance was covered by teams that lost set 5 after winning the previous set.